Landslide Risk on the Farmland at the Arjuno Volcano Complex of East Java - Purnomo, Nugroho Hari; Sutikno, S; Sunarto, S (Universitas Muhammadiyah Surakarta, 2013)
The purposes of the study are (1) studying the characteristics of the landslide hazard level, vulnerability, and capacity dealing with the seasonal plant farmland, and (2) developing the conceptual model disaster risk of landslide for the seasonal plant farmland at the stato volcano area. Sampling of the land factor was carried out in a purposive way and the sampling of the people was carried out accidentally. The analysis was conducted descriptively, parametric and non-parametric statistics, and spatial analysis of ecological map, land shape, slope, soil and land use. The findings showed that the extremely high landslide risk occurred at the cone shape of the incised volcano and the slope of the incised volcano. The economic vulnerability of one-seasonal crop farmland was about Rp. 8,879,310 ha/year-Rp. 44,036,061 ha/year. While, the socio-economic factor of the farmers was generally characterized by a transition into a periurban area. The conceptual model tated that the resources of seasonal plant farmland with the high risk of landslide can be cultivated with the acceptable risk if the vulnerability of agricultural commodity is low in economic value and the capacity of farmers cultivating it is high.